Socio-cultural determinants of physical activity across the life course: a 'Determinants of Diet and Physical Activity' (DEDIPAC) umbrella systematic literature review - Lina Jaeschke; Astrid Steinbrecher; Agnes Luzak; Anna Puggina; Katina Aleksovska; Christoph Buck; Con Burns; Greet Cardon; Angela Carlin; Simon Chantal; Donatella Ciarapica; Giancarlo Condello; et al. (BMC, 2017)
Abstract Objective Regular physical activity (PA) reduces the risk of disease and premature death. Knowing factors associated with PA might help reducing the disease and economic burden caused by low activity. Studies suggest that socio-cultural factors may affect PA, but systematic overviews of findings across the life course are scarce. This umbrella systematic literature review (SLR) summarizes and evaluates available evidence on socio-cultural determinants of PA in children, adolescents, and adults. Methods This manuscript was drafted following the recommendations of the 'Preferred Reporting Items for Systematic reviews and Meta-Analyses' (PRISMA) checklist. The MEDLINE, Web of Science, Scopus, and SPORTDiscus databases were searched for SLRs and meta-analyses (MAs) on observational studies published in English that assessed PA determinants between January 2004 and April 2016. The methodological quality was assessed and relevant information on socio-cultural determinants and any associations with PA was extracted. The available evidence was evaluated based on the importance of potential determinants and the strength of the evidence. Results Twenty SLRs and three MAs encompassing 657 eligible primary studies investigated potential socio-cultural PA determinants, with predominantly moderate methodological quality. Twenty-nine potential PA determinants were identified that were primarily assessed in children and adolescents and investigated the micro-environmental home/household level. We found probable evidence that receiving encouragement from significant others and having a companion for PA were associated with higher PA in children and adolescents, and that parental marital status (living with partner) and experiencing parental modeling were not associated with PA in children. Evidence for the other potential determinants was limited, suggestive, or non-conclusive. In adults, quantitative and conclusive data were scarce. Conclusions A substantial number of SLRs and MAs investigating potential socio-cultural determinants of PA were identified. Our data suggest that receiving social support from significant others may increase PA levels in children and adolescents, whereas parental marital status is not a determinant in children. Evidence for other potential determinants was limited. This was mainly due to inconsistencies in results on potential socio-cultural determinants of PA across reviews and studies. Trial registrations This umbrella SLR was recorded on PROSPERO (Record ID: CRD42015010616 ).